2021
DOI: 10.1159/000516340
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Leukocytosis Predicts Cognitive Decline but Not Behavioral Disturbances: A Nationwide Study of Alzheimer’s and Parkinson’s Disease Patients

Abstract: <b><i>Introduction:</i></b> Peripheral and central nervous system inflammation have been linked to the classic symptoms of Parkinson’s disease (PD) and Alzheimer’s disease (AD). However, it remains unclear whether the analysis of routine systemic inflammatory markers could represent a useful prediction tool to identify clinical subtypes in patients with Parkinson’s and Alzheimer’s at higher risk of dementia-associated symptoms, such as behavioral and psychological symptoms of dementia (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Furthermore, this study examined the correlation between blood and urine biomarkers and aMCI. Previous studies 37 have reported leukocytosis as an independent risk factor for Parkinson's disease, while other studies have found no signi cant difference in white blood cell (WBC) counts between the MCI group and the normal group 22 . It remains unclear whether the analysis of systemic in ammatory markers, represented by white blood cells, can serve as a useful indicator for predicting MCI.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, this study examined the correlation between blood and urine biomarkers and aMCI. Previous studies 37 have reported leukocytosis as an independent risk factor for Parkinson's disease, while other studies have found no signi cant difference in white blood cell (WBC) counts between the MCI group and the normal group 22 . It remains unclear whether the analysis of systemic in ammatory markers, represented by white blood cells, can serve as a useful indicator for predicting MCI.…”
Section: Discussionmentioning
confidence: 95%
“…Inflammation of the peripheral and central nervous system leads to the classic symptoms of Alzheimer’s disease (AD) [ 92 ]. A recent study identified that the gut microbiome has a significant impact on the disease pathology in an AD mouse model (5xFAD).…”
Section: The Pre and Clinical Neurological Effect Of Probioticsmentioning
confidence: 99%